(untitled) (Journal of Ideas in Health, 2021)
Background: CHA2DS2-VASc score is a scientifically proven risk assessment score for patients with atrial fibrillation. It may be a good predictor of in-hospital death in COVID-19 patients. The present study aimed to evaluate the association between CHA2DS2-VASc score and in-hospital mortality in the prognosis of intensive care unit (ICU) patients with COVID-19. Methods: Eighty-four COVID-19 patients who were hospitalized in the ICU were retrospectively analyzed in a tertiary health care center, and the CHA2DS2-VASc score was determined. All analyses were performed using SPSS statistical software (SPSS Inc., Chicago, IL, USA, 20.0). A p-value <0.05 was considered statistically significant. Results: The median age of patients was 60.0 years, and most were males (75.0%). Findings of the study showed that the CHA2DS2-VASc score was considerably higher among the hospitalized patients than discharged patients (3.08 ± 1.72 vs. 1.38 ± 1.16; p<0.001), and patients who required mechanical ventilation compared to those who did not require mechanical ventilation (3.03 ± 1.68 vs. 1.15 ± 0.97; P <0.001), respectively. Patients with CHA2DS2-VASc score of ≥3 had substantially higher age [67(45-87) vs. 58(19-75); P ˂0.001], computed tomography involvement score [67.5(20-90) vs. 35(15-90); P ˂0.001] and need for mechanical ventilation [29(90.6%) vs. 22(42.3%); P ˂0.001]. A significant difference was found in oxygen saturation on admission (P =0.001) between the two groups. In-hospital death was significantly higher among patients with a CHA2DS2-VASc score of ≥3 (P <0.001). The CHA2DS2-VASc score was positively correlated with white blood cells count (r=0.257, P =0.018) and negatively correlated with the number of days spent in the hospital (r=-0.184, P=0.130) due to higher in-hospital death in ICU patients with COVID-19. Conclusion: CHA2DS2-VASc score may be an effective tool to estimate in-hospital death in COVID-19 patients who were hospitalized in the ICU.